2013
DOI: 10.3174/ajnr.a3784
|View full text |Cite
|
Sign up to set email alerts
|

Metrics and Textural Features of MRI Diffusion to Improve Classification of Pediatric Posterior Fossa Tumors

Abstract: BACKGROUND AND PURPOSE:Qualitative radiologic MR imaging review affords limited differentiation among types of pediatric posterior fossa brain tumors and cannot detect histologic or molecular subtypes, which could help to stratify treatment. This study aimed to improve current posterior fossa discrimination of histologic tumor type by using support vector machine classifiers on quantitative MR imaging features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 26 publications
4
83
0
Order By: Relevance
“…In the majority of recent studies employing quantitative image feature assessment for gliomas, only 1 category feature from 1 MRI sequence, such as texture, was applied [16,25], which provided limited information. In this study we investigated the efficiency of radiomic features from multiple MRI sequences for gliomas grading, yielding promising results.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of recent studies employing quantitative image feature assessment for gliomas, only 1 category feature from 1 MRI sequence, such as texture, was applied [16,25], which provided limited information. In this study we investigated the efficiency of radiomic features from multiple MRI sequences for gliomas grading, yielding promising results.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,15,16 Several of these studies used DWI to distinguish between different types of paediatric posterior fossa tumours, but there were many limitations [14][15][16][17][18] . To our knowledge, the present study is the first to have specifically sought to grade ependymomas in children.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional T1‐ and T2‐weighted magnetic resonance imaging (MRI) is essential for diagnosis and evaluation of tumor location, extent, and involvement of eloquent brain regions, but does not reliably differentiate between the various tumor grades and types . Several studies have shown that the diffusion characteristics may be helpful in narrowing down the preoperative diagnosis . Previous studies used quantitative apparent diffusion coefficient (ADC) measurements to differentiate the various grades and histological subtypes of cerebellar tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies used quantitative apparent diffusion coefficient (ADC) measurements to differentiate the various grades and histological subtypes of cerebellar tumors. ADC values were typically measured in the solid, contrast enhancing component of the tumor (SCT) . This approach, however, has several limitations.…”
Section: Introductionmentioning
confidence: 99%